Effect of Na doping on the properties of ZnS thin films and ZnS/Si heterojunction cells - Yesilkaya, S. Serkis; Ulutas, Unzile; Abd Alqader, Huda M. (ELSEVIER, 2021)
Undoped and 1, 5, 10 and 15% sodium doped ZnS thin films were grown on glass and Si substrates by spray pyrolysis. Effect of Na doping on the properties of ZnS thin films were investigated via XRD, SEM, UV-Visible spectrometry and resistivity measurements. Photovoltaic behavior of ZnS/Si heterostructure cells were investigated by current-voltage measurements. Band gap energy of ZnS film was decreased to 3.42 eV from 3.66 eV and resistivity of the film was decreased to 2.00 x 10(5) Omega.cm from 5.17 x 10(5) Omega.cm with increasing Na doping concentration. Photovoltaic performance of ZnS/Si heterostructure cell was improved and power conversion efficiency was increased to 5.06% from 2.20%. (C) 2021 Elsevier B.V. All rights reserved.
Keywords: ZnS; Thin films; Na doping; Semiconductors; SPRAY-PYROLYSIS; SI; Materials Science; Physics